2005
DOI: 10.1080/09540120500100890
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and African immigrant women in Philadelphia: Structural and cultural barriers to care

Abstract: Although African immigration to American cities is increasing, there is little published demographic or epidemiological data on this population. As growing numbers of HIV-positive Africans seek care at public health centres in the city of Philadelphia, medical personnel are confronted with the challenges of serving this population. This qualitative study explores the perspectives of HIV service providers who are treating this new patient group, and it examines the cultural and structural barriers African women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
119
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(126 citation statements)
references
References 12 publications
7
119
0
Order By: Relevance
“…Recent immigrants to Canada face several obstacles including language barriers, cultural differences, uncertain immigration status, and employment and housing issues (3,(7)(8)(9)). An HIV diagnosis adds an additional stress, and gaining access to care and treatment provides additional challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Recent immigrants to Canada face several obstacles including language barriers, cultural differences, uncertain immigration status, and employment and housing issues (3,(7)(8)(9)). An HIV diagnosis adds an additional stress, and gaining access to care and treatment provides additional challenges.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Homelessness has been found to be associated with retention, 7 as has lack of transportation, perceived stigma, 8 lack of HIV awareness, fear of the healthcare system, and legal status for immigrants. 3 Financial barriers, the extent of coverage and out of pocket costs have also kept HIV + individuals from engaging in care, 2,9 as have concerns about whether clinics are known in the community as an HIV/AIDS treatment program, and how the organization is structured to provide care. 8,9 Medication adherence has also been affected by the side effects, dosage schedule, and the effects taking medications may have on interpersonal relationships.…”
mentioning
confidence: 99%
“…Although the role of higher education in understanding HIV infection is debatable, education may facilitate behavior change and promote the adoption of safer sexual behaviors, including condom use [36,51,63]. In their review, Hargreaves and Glynn concluded that new HIV infections were increasingly seen among less educated women [61].…”
Section: Discussionmentioning
confidence: 99%
“…Systems factors in Omaha may have affected the women's ability to access voluntary counseling and testing for HIV. Often, structural, cultural, and linguistic barriers; stigma; discrimination; xenophobia; and exploitation decrease or discourage access to HIV/AIDS education or health services [6,[15][16][17][18][19][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation